Application of Project Based Learning Methods to Increase Student Activity and Creativity: Penerapan Metode Pembelajaran Project Based Learning untuk Meningkatkan Keaktifan dan Kreatifitas Siswa - Ibnu Sudarmadi (Perkumpulan Doktor Indonesia Maju (PDIM), 2022)
The hallmark of modern education today is that students must be able to participate actively and creatively by incorporating the intellectual and emotional aspects of students into the learning process. Thus, it can be translated that in every learning of graphic skills, these skills must be directed at developing the operational capacity of students both mentally and physically. From observations and interviews with teachers and students of class XI MM SMK Negeri 7 Sijunjung, it was found that learning was still a bit monotonous, some teachers carried out the teaching and learning process through games, demonstrations, videos, and students followed the teacher's instructions, and some students seemed less active and creative in developing their respective innovations so that the lesson feels unattractive to students. Project Based Learning (PjBL) learning model is a way of teaching material by directing students to project implementation and students can be actively and creatively involved in the teaching and learning process, thereby destroying the learning atmosphere to be alive. This research consisted of 2 cycles, each of which consisted of planning, implementing actions, observing, and reflecting. The implementation of actions using internet media and the use of other Information Technology equipment by the method of giving project assignments to students. The results showed that at the end of the second cycle, the average activity and creativity increased steadily from one meeting to the next.